Upaya Peningkatan Psikomotorik Siswa Pada Lari 100 Meter Dengan Permainan Estafet Bola Di Kelas XI.4 SMA Negeri 11 Semarang (psnppg, 2025)
The purpose of this study is to improve students' psychomotor skills through education with ball relay games on the 100-meter running material in class XI.4 of SMA Negeri 11 Semarang. This research is a classroom action research conducted in two cycles. This research was conducted in semester 2, academic year 2024/2025 in March to May with a total of 36 students. Data collection techniques through observation, interviews and practical tests. Data analysis techniques in the form of descriptive analysis through observation of students in participating in 100-meter running learning on the psychomotor aspect. The results of this study indicate that students' psychomotor scores in the pre-cycle had a completion rate of 57.7% with an average score of 60.69. In cycle I, the completion rate was 72.2% with an average score of 73,33. In cycle II, there was an increase in completion rate of 80.5% with an average score of 79,33.  In this study, the results showed that using the ball relay game approach can improve psychomotor skills for students.
Keywords: Psychomotor; run; ball relay